A promising perovskite primary explosive - Feng, Yongan; Zhang, Jichuan; Cao, Weiguo; Zhang, Jiaheng; Shreeve, Jean’ne M. (Nature communications, 2023)
A primary explosive is an ideal chemical substance for performing ignition in military and commercial applications. For over 150 years, nearly all of the developed primary explosives have suffered from various issues, such as troublesome syntheses, high toxicity, poor stability or/and weak ignition performance. Now we report an interesting example of a primary explosive with double perovskite framework, {(C 6 H 14 N 2 ) 2 [Na(NH 4 )(IO 4 ) 6 ]} n ( DPPE-1 ), which was synthesized using a simple green one-pot method in an aqueous solution at room temperature. DPPE-1 is free of heavy metals, toxic organic components, and doesn’t involve any explosive precursors. It exhibits good stability towards air, moisture, sunlight, and heat and has acceptable mechanical sensitivities. It affords ignition performance on par with the most powerful primary explosives reported to date. DPPE-1 promises to meet the challenges existing with current primary explosives, and this work could trigger more extensive applications of perovskite. A primary explosive (DPPE-1) with a double perovskite structure and ignition function was reported. It is synthesized in a straightforward manner and has good stability, with a minimum primary charge of 5 mg.